Toll-like receptor expression in the nervous system of bovine alpha-herpesvirus-infected calves - Marin, Maia Solange (2014)
In this study, the expression levels of viral Toll-like receptors (TLRs) in the nervous system of bovine herpesvirus type 5 (BoHV-5)-infected calves were investigated. A significant increase in the expression of TLRs 3 and 7–9 was found in the anterior cerebral cortex during acute infection and viral reactivation. In the trigeminal ganglia, only TLR9 expression was significantly affected. The magnitude of the increase was lower in BoHV-1-infected calves, suggesting that a restricted immune response might protect against exacerbated inflammatory responses in the brain. This work describes, for the first time, the involvement of TLRs 3 and 7–9 in the recognition of BoHV in the bovine nervous system, indicating that the expression of these receptors might be associated with the development of neurological disease. Modulation of the signalling pathways mediated by TLRs might provide an effective approach to control the neuro-immune response to BoHV-5, which may be responsible for neurological lesions.